Respuesta :
Answer:
y - 13 = 2(x - 4).
Step-by-step explanation:
The slope = (y2 - y1)/ (x2 - x1)
Here y2 = 13, y1 = 1, s2 = 4 and x1 = -2.
The slope = (13 - 1)/ ( 4 - -2)
= 12/6
= 2.
Point slope form is
y - y1 = m(x - x1) where m = slope (= 2) and we take the point (4, 13) for
(x1, y1):
y - 13 = 2(x - 4) is the required equation.
The answer is : 2x - y + 5
The explanation is given below :
The formula for the equation in point slope form is :
y -y1 = m(x-x1) where m= (y2-y1)/(x2-x1)
Using the given points we have the values , y1 =1 , y2=13. , x1= -2 , x2 = 4
Thus putting the values ;
y-1 = (13-1)/4-(-2) [x-(-2)]
Y-1 = 12/6(x+2)
Y-1=2(x+2)
Y-1 = 2x +4
Taking the value on the right side ,
0= 2x-y+5
And thus the required equation
Hope it is well understood to you !
The explanation is given below :
The formula for the equation in point slope form is :
y -y1 = m(x-x1) where m= (y2-y1)/(x2-x1)
Using the given points we have the values , y1 =1 , y2=13. , x1= -2 , x2 = 4
Thus putting the values ;
y-1 = (13-1)/4-(-2) [x-(-2)]
Y-1 = 12/6(x+2)
Y-1=2(x+2)
Y-1 = 2x +4
Taking the value on the right side ,
0= 2x-y+5
And thus the required equation
Hope it is well understood to you !